Aplikasi E-Kafe Green Market Padang Berbasis Web - Zainul Efendy; Mia Nurhayati Idris (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
Transaction and promotion processes are very important in a trading activity, so it takes a system or application to manage the process to be more efficient. This research aims to produce an application that can provide transaction and promotion service solutions in Padang green market cafes. Application development methods use prototypes with problem analysis stages, creating application design models and testing. Hierarchy input process output (HIPO) is a diagram that is a design application that has been created starting from data entry, data process, and reports. Entity Relationship Diagram (ERD) and Context Diagram (CD) are to model data structures and relationships between data. Furthermore, this system evalusion is tested using blackbox testing that serves to find out how far the component components or modules on the system are working. The results of this research are in the form of applications or information systems to facilitate the transaction process at Kafe Green Market Padang. The system consists of the main page, login page, data entry menu, transaction menu, and payment confirmation menu. The evaluation results show that the system is already running well, because every component of the system when used there is no error. So that this system can be used and utilized by users.